Investigating the decision-making process for the establishment of a seaport in Cape Fria, Namibia With a focus on Driving Factors, Stakeholder Management, and Project Evaluation - Liswaniso, Georgina (2013)
The purpose of this dissertation is to explore certain aspects of the decision-making process used to establish a seaport in a country. A public infrastructure project such as a seaport requires extensive planning, investment, and cooperation of various stakeholders involved. This study investigates what type of factors motivate the prospect of building a port, what are the methods used in managing the relevant stakeholders and how the project can be evaluated. These research questions were answered by the review of literature and through practical research involving a case study with the Namibian Ministry of Works, Transport and Communication. The practical research consisted of a structured telephone interview and a review of a pre-feasibility study. The research questions were fulfilled through a number of key findings. Firstly, the main driving factors for building a port in Cape Fria are recently discovered minerals that have export potential, the exploration of oil and gas and their potential, and the potential development of tourism in the region. These factors would enable development of the region, transport infrastructure and the employability of the local community. Secondly, stakeholders were identified based on their involvement in the project and are managed based on the power and knowledge of the driving factors they are involved in. Finally, the cost-benefit analysis was used to evaluate the project; the capital budgeting approach was used. One of the main conclusions drawn from this research is that the Cape Fria area in the Kunene region was chosen chiefly for the commodities that are based there and have mining and export potential. These commodities, especially the minerals, have the capability to provide economic benefit to the region and the country as a whole. As the prioritisation of stakeholders and their interests are based on their responsibility over the driving factors, the interests and development of the local community can be lost. It is therefore recommended that greater participation be given to the local community as stakeholders, and improved plans be made on how to ensure they receive the highest benefit from the project through structured training for employment and support for new businesses.